Blocking antibodies induced by peanut oral and sublingual immunotherapy suppress basophil activation and are associated with sustained unresponsiveness. Issue 4 (29th November 2018) - Orgel, Kelly; Burk, Caitlin; Smeekens, Johanna; Suber, Jada; Hardy, Lakeya; Guo, Rishu; Burks, A. Wesley; Kulis, Michael
Abstract: Background: Oral and sublingual immunotherapies for peanut allergy have demonstrated efficacy in small clinical trials; however, mechanisms and biomarkers correlating with clinical outcomes remain elusive. Previous studies have demonstrated a role for IgG in post‐OIT plasma in the suppression of IgE‐mediated mast cell reactions. Objective: The aim of this study was to characterize the role that peanut oral and sublingual immunotherapy‐induced plasma factors play in the inhibition of ex vivo basophil activation and whether inhibitory activity is associated with clinical outcomes. Methods: Plasma samples from subjects on placebo, peanut oral immunotherapy (OIT) or peanut sublingual immunotherapy (SLIT), and IgG‐depleted plasma or the IgG fraction were incubated with sensitized basophils, and the inhibition of basophil activation following stimulation with peanut extract was measured. Basophil inhibition results were compared between the two routes of immunotherapy, time on treatment and clinical outcomes. Results: Plasma from subjects after 12 months of active peanut OIT, but not placebo, inhibits basophil activation ex vivo . Depletion of IgG abrogated the blocking effect of OIT plasma, while the IgG fraction substantially blocked basophil activation. Basophils are inhibited to a similar extent by undiluted OIT and SLIT plasma; however, diluted OIT plasma from the time of desensitization challenge inhibited basophils more than diluted SLIT plasma from time of desensitization challenge. Plasma from subjects who experienced sustained unresponsiveness following OIT inhibited basophils to a greater extent than plasma from subjects who were desensitized, but this was not true for SLIT. Conclusions and Clinical Relevance: Peanut immunotherapy induces IgG‐dependent functional changes in plasma that are associated with OIT but not SLIT clinical outcomes. Understanding the mechanisms of peanut OIT and SLIT may help derive informative biomarkers.